Upaya Manajemen dalam Meningkatkan Kualitas Pelayanan Pramusaji di Café Del Mar Canggu Bali - Ni Komang Suriani; I Gusti Nyoman Wiantara; Ida Ayu Putu Sulastri (CV Global Research Publication, 2026)
This study examines the gap between expected and actual service quality and analyzes the role of management in improving waiter performance at Café del Mar Canggu Bali. This research addresses this gap by integrating the SERVQUAL framework with management functions to understand service quality as an outcome of organizational practices.This study employs a qualitative descriptive approach. Data were collected through observation, in-depth interviews, and documentation involving managers, supervisors, and waiters directly engaged in service operations. The data were analyzed to identify patterns of service inconsistency and managerial responses in addressing operational challenges.The findings reveal that service quality gaps primarily occur in responsiveness, reliability, and empathy dimensions, particularly during peak operational conditions. These issues are not solely caused by individual performance, but are also linked to coordination weaknesses, uneven competency distribution, and limitations in training implementation. Management responses include training programs, daily briefings, supervision, performance evaluation, and SOP enforcement, supported by operational adjustments such as staff addition during peak seasons and improved team communication. The study highlights that service quality consistency is strongly influenced by the integration of managerial systems and operational execution.This research contributes to hospitality management literature by extending SERVQUAL analysis through a managerial process perspective, positioning service quality as a systemic outcome rather than an individual performance issue.